Border carbon adjustments: Should production or consumption be taxed? - Martin, Will (Cambridge University Press, 2023)
Border Carbon Adjustments (BCAs) may play an important role in lowering the economic costs of greenhouse gas mitigation and in overcoming political-economy constraints on the use of carbon taxes or equivalent measures. A carbon tax plus a full BCA could deal with the competitiveness challenges arising from carbon taxes by using the WTO's National Treatment principle to apply equal levies on domestic production and on imports, and by symmetrically rebating the carbon tax on exports in the manner of a value-added tax (VAT) export rebate. This approach would shift the base for carbon taxation from production to demand and potentially achieve substantial reductions in the cost of cutting emissions. It would avoid the massive measurement and compliance problems associated with BCAs based on foreign emission intensities. By contrast, import-only BCAs distort prices of importables relative to exportables; create divisive trade conflicts and deterioration in the terms of trade for developing countries; and likely require development of complex sets of import preferences.